Misalignments in prepaid water technology: findings from urban poor settings of Kampala, Uganda - Ahabwe, Gerald Zihembire; Ssewaya, Achilles; Batega, Dauda Waiswa; Kayaga, Sam (IWA Publishers, 2024)
ABSTRACT Progressive urban water utilities in developing countries have, since the mid-2000s deployed prepaid dispensers (PPDs) to provide reliable and equitably priced water services to slum residents. This paper reports on a study that evaluates the performance of the PPDs first deployed in the slums of Kampala in 2006 by the National Water and Sewerage Corporation (NWSC), Uganda's main urban water utility. By February 2020, over 1,400 PPDs were installed in 20 slums, serving residents through over 33,000 access tokens. Data were collected in 2019/2020 through 275 household questionnaires, 17 key informant interviews, and 8 focus group discussions. The main finding was that although the PPD technology has achieved a relatively high diffusion rate, water drawn therefrom was an average of a paltry 7 litres per capita per day, meaning that many slum residents still rely on other water sources of doubtful quality. Key misalignments include misappropriation by local middlemen, who inflate the prices; high levels of technical malfunctions; and the utility's overreliance on international development financing for asset maintenance and expansion. NWSC should mainstream the pro-poor service department and build the necessary capabilities to ensure better technical functionality of the PPDs, including setting up smart partnerships where necessary. CrossRef